Minimizing the Diagnostic Delay in Amyotrophic Lateral Sclerosis: The Role of Nonneurologist Practitioners - Martin Matharan; Stéphane Mathis; Sarah Bonabaud; Louis Carla; Antoine Soulages; Gwendal Le Masson (Neurology Research International)
Introduction. Amyotrophic lateral sclerosis (ALS), usually fatal in a few years, is a neurodegenerative disorder where the diagnostic delay, although variable according to the studies, remains too long. The main objective of this study was to determine the average time to diagnose ALS and the role of each physician, general practitioner (GP), or specialist (neurologist or not) involved in the management of these patients. The secondary objective was to propose some simple schemes to quickly identify an ALS suspicion with the aim to reduce this delay. Patients and Methods. This retrospective study evaluated the diagnostic delay (and other intermediate delays) of 90 ALS patients registered in the ALS Center of Bordeaux (France) in 2013. The main clinical signs encountered (and their order of appearance) were studied. Results. The average diagnostic delay was 17 months, with a median diagnostic delay of 12 months. The average diagnostic delay was 2.7 months between the first symptoms and the first complaint to GP, followed by an additional 6.5 month delay before the patient’s first visit to a neurologist. This period could be shortened, especially if GP performed additional tests quickly (p=0.01), as the time spent consulting various specialists often extends this crucial step. Overall, diagnostic delay accounted for 40% of the total duration of the disease progression. Conclusion. In relation to total survival time, the diagnostic delay of ALS appears to be proportionately very long, sometimes longer than that observed in previous studies (because it also included the total delay to diagnostic or treatment initiation). The rapid execution of useful additional tests by the first medical doctor, often GP (with the help of a neurologist), considerably reduces the diagnostic delay. The central role of GP seems to be crucial in the management of patients with ALS. The main objective is, of course, to initiate appropriate treatment and care as soon as possible. Finally, based on our results, we also provide a short practical diagram to help nonneurologist practitioners to quickly discuss the diagnosis of ALS in case of some specific symptoms (“red flags”).